Regional integration in Africa: Challenges and prospects - Jaime De Melo; Yvonne Tsikata (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
Political motives, geography, and the uneven distribution of gains trumped the traditional efficiency gains across Africa's Regional Economic Communities (RECs). The small, sparsely populated, fragmented, and often isolated economies across Africa make a compelling case for these economies to integrate regionally to reap efficiency gains, exploit economies of scale, and reduce the thickness of borders. But lack of complementarities among partners and diminishing returns to the exploitation of resources has reduced supply response to market-integration-oriented regional policies. Additionally, a very uneven distribution of resources has sharpened the trade-off between the benefits of common policies needed to tackle cross-border externalities and their costs, which are heightened by the sharp differences in policy preferences across members. African RECs have pursued the 'linear model' of integration with a stepwise integration of goods, labour, and capital markets, as well as eventual monetary and fiscal integration. With the exception of the franc zone, the RECs have not yet completed goods-markets integration; the lack of adjustment funds to address the uneven distribution of benefits across partners contributing to the delay. Estimates reported here reveal the shortcomings of the linear model of integration, as behind-the-border measures aiming to reduce trade costs were largely ignored across African RECs until recently. While this is probably due to the difficulty in gaining the confidence necessary to get collection action started, many behind-the-border measures could still have been undertaken unilaterally.
Keywords: F6; F12; F15; F16; 330; regional integration; Africa; trade creation; trade diversion; Franc zone; trade liberalization